Research of structure and sorption properties of montmorillonite modified with hexadecylthymethylammonium bromide - Zhdanyuk, Nataliya; Chudinovych, Olga (Technology audit and production reserves, 2019)
The object of research is a natural layered silicate – montmorillonite of the Cherkasy deposit (Ukraine) with the general formula (Ca,Na)(А1,Mg,Fe)2(OH)2[(Si,А1)4О10]×nH2O. The chemical composition of the mineral: SiO2 – 51.9 %, Аl2O3 – 17.10 %, Fe2O3 – 7.92 %, MgO – 1.18 %, Na2O, K2O and CaO up to 2 % and Н2О – 8.78 %. Montmorillonite is characterized by a significant dispersion of particles and the presence of a large number of sorption centers on its surface is capable of cation exchange. One of the most problematic places is that montmorillonite is practically incapable of removing pollutants present in water as anions. In order to obtain sorbents capable of removing heavy metal anions, the surface of montmorillonite was modified with the cationic surfactant hexadecyltrimethylammonium bromide. During the study, X-ray diffraction analysis, scanning electron microscopy, infrared spectroscopy, and thermal analysis were used to study the structure of the initial montmorillonite and its organomodified forms. The spectrophotocolorimetric method is used to study the sorption properties of composites. The work confirms that hexadecyltrimethylammonium bromide molecules are sorbed not only on the outer surface of the particles, but also migrate between the aluminosilicate packets of the layered structure of montmorillonite. Sorption studies have confirmed that the use of organomodified forms of montmorillonite has increased the degree of extraction of chromium (VI) ions from 32 % to 96 %. The resulting sorbents make it possible to purify contaminated water with a chromium (VI) concentration of 1 mg/dm3 to the maximum permissible concentrations. This is due to the fact that the organomodification of the surface of montmorillonite has a number of features and allows to change the structure of the original mineral, as well as recharge the clay surface from negative to positive. This makes it possible to use organoclay to remove inorganic toxicants in anionic forms. Compared with similar known ones, the obtained composites provide the removal of even trace amounts of heavy metal anions from aqueous media.